Rural Women's Perceptions of Availability, Development and Maintenance of Rural Built Environments - Jeanine E Gangeness (Rural Nurse Organization; Binghamton University, 2012)
Background: Obesity is a worldwide concern. Physical activity is one way to address obesity. The environment surrounding individuals can impact activity choices. Design/Methods: Multiple, description, explanatory case study design, multiple-methods (focus groups, individual interviews, archival data collection, sidewalk maintenance evaluation) Findings: Women participants perceived community economic resources as an influencing factor for availability, development, and maintenance of rural built environments conducive to physical activity. These women participants also identified women speaking out and "being heard‟ as influencing availability and maintenance of built environments, and advancing age with reduced physical ability influenced the maintenance of resident-owned rural built environments. Conclusions: There are many policy indications for local nurses advocating for rural populations including the consideration of built environment as a factor in health promotion and treatment (diabetes, obesity).